Pengaruh Kepadatan Azolla Sp. Yang Berbeda Terhadap Kualitas Air Dan Pertumbuhan Benih Ikan Lele Dumbo (Clarias Gariepinus) Pada Sistem Tanpa Ganti Air - Sitompul, Sasty Osuna; Harpeni, Esti; Putri, Berta (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2012)
The aims of this research were to determine the effect of Azolla sp. to water quality and the growth of African catfish (Clarias gariepinus) juvenile (total length 5-7 cm) cultured with closed water system. The study used five treatments of density of Azolla sp. (0g/m2, 62.5 g/m2, 125 g/m2, 187.5 g/m2, and 250g/m2). The observations towards water quality and growth parameter were pH, temperature, dissolved oxygen, ammonia, absolute weight growth, absolute growth rate, and survival rate. The results showed that the addition of Azolla sp. provided a significantly different affect to pH, absolute growth weight, daily growth rate, and survival. Survival rate and pH showed that density of 0g/m2 of Azolla sp. significantly different densities to other treatments. Absolute growth weight and daily growth rate of African catfish showed that density of 0g/m2of Azolla sp. significantly different to densities of 62.5g/m2, 125 g/m2, 187.5g/m2, except for the density 250g/m2. Based on temperature, dissolved oxygen, pH, survival rate and daily growth rate of African catfish and Azolla sp. occured at density of 125g/m2 of Azolla sp.